The correlation between the intensity of benzene exposure and complete blood count in the oil and natural gas company workers in East Kalimantan - Ngatidjan, Idha Arfianti Wiraagni Iwan Dwiprahasto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Benzene is one of the dangerous chemical substances which can cause some health disturbances.Meta-analysis shows that people who are exposed to benzene have a leukemia risk of 1.4 timesmore than the ones who are not. The employees who are exposed to benzene for a long timehave a probability to receive the toxic effect from benzene. This study was conducted to evaluatethe relationship between the intensity of benzene exposure and blood count of employees in theoil and natural gas company in East Kalimantan. This research was conducted to 897 employeeswith case control design. The control group consisted of 521 subjects, whereas the case groupconsisted of 376 subjects. The subjects were 39.91Â±10.90 years old, with the working termbetween 1 to 36 years. Data were obtained from routine medical check-up and health riskassessment in 2007 â 2010. The independent variable namely benzene exposure and the dependentvariable namely result of blood count, were analyzed by using chi-square bivariat analysis.Intensity of benzene exposure was measured as OVM (Organic Vapour Monitor) for externaldosage and SPMA (S-phenylmercapturic acid) for internal dosage. The intensity of benzene in2007 was 1.07Â± 5.5 ppm (OVM) and average of SPMA was 11.54Â±5.28 Ã¬g/g creatinine. Theintensity of benzene in 2009 was 4.15Â±13.6 ppm (OVM) and SPMA was 55.90Â±43.6 Ã¬g/gcreatinine. The employees who were exposed to benzene had a risk of having a decrease ofeither hemoglobin, erythrocyte, thrombocyte, or leukocyte 1.71 times (95% CI, 1.18â2.48)compared with the control, although this reduction was still in the normal range (p= 0.004). Inconclusion, there was no relationship between the intensity of benzene exposure with the lowblood count of the employees.Keywords: benzene exposure - complete blood counts - oil and gas earth - mining - toxic effect